No conventional cereals, tricepiro (Triticum x Secale x Thrinopyrum) y triticale (Triticum x Secale) utilization in pigs feedeng. Two experiences. (Semiárida, 2020)
The objective of these experiments was to study the different cereal grains ("tricepiro and trilicale") as energy sourees in growing-finishing diets. The hybrid gilts (Yorl
Keywords: tricepiro; triticale; feeding diets; growing-finishing gilts